Site-Specific Mutational Analysis of a Novel Cysteine Motif Proposed To Ligate the 4Fe-4S Cluster in the Iron-Sulfur Flavoprotein of the Thermophilic Methanoarchaeon Methanosarcina thermophila - Leartsakulpanich, Ubolsree (American Society for Microbiology, 2000)
Isf (iron-sulfur flavoprotein) from Methanosarcina thermophila has been produced in Escherichia coli as a dimer containing two 4Fe-4S clusters and two FMN (flavin mononucleotide) cofactors. The deduced sequence of Isf contains six cysteines (Cys 16, Cys 47, Cys 50, Cys 53, Cys 59, and Cys 180), four of which (Cys 47, Cys 50, Cys 53, and Cys 59) comprise a motif with high identity to a motif (CX(2)CX(2)CX(4–7)C) present in all homologous Isf sequences available in the databases. The spacing of the motif is highly compact and atypical of motifs coordinating known 4Fe-4S clusters; therefore, all six cysteines in Isf from M. thermophila were altered to either alanine or serine to obtain corroborating biochemical evidence that the motif coordinates the 4Fe-4S cluster and to further characterize properties of the cluster dependent on ligation. All except the C16S variant were produced in inclusion bodies and were void of iron-sulfur clusters and FMN. Reconstitution of the iron-sulfur cluster and FMN was attempted for each variant. The UV-visible spectra of all reconstituted variants indicated the presence of iron-sulfur clusters and FMN. The reduced C16A/S variants showed the same electron paramagnetic resonance (EPR) spectra as wild-type Isf, whereas the reduced C180A/S variants showed EPR spectra identical to those of one of the two 4Fe-4S species present in the wild-type Isf spectrum. Conversely, EPR spectra of the oxidized C50A and C59A variants showed g values characteristic of a 3Fe-4S cluster. The spectra of the C47A and C53A variants indicated a 4Fe-4S cluster with g values and linewidths different from those for the wild type. The combined results of this study support a role for the novel CX(2)CX(2)CX(4–7)C motif in ligating the 4Fe-4S clusters in Isf and Isf homologues.